THE ROLE OF GAMES IN TEACHING FOREIGN LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This article reveals the role of using games in the process of teaching foreign languages at school. It also provides definitions for the concept of “game” by different methodologists. The article describes the various types and forms of games used in English lessons at school, identifies the goals, functions, lists the factors influencing the conduct of the game and highlights methodological aspects. It is noted that the game is an integral part of the process of learning a foreign language at the initial stage.